The contribution of headmaster’s personality competence to the teacher’s social competence of vocational high school - Nellitawati, Nellitawati (COUNS-EDU: The International Journal of Counseling and Education, 2017)
This research aims to know the contribution of headmaster’s personality competence to the teacher’s social competence at Vocational High School. The type of this research is Correlation. With 55 teachers at the State of Vocational High School in Padang Municipality through sampling technique of stratified random sampling. The used of the instrument is scale of KKPS and KSG. Test Instrument covers testing validity and reliability. The analysis of data uses correlation. The result of this research are: (1) headmaster’s personality competence teacher of the State of Vocational High School 6 in Padang Municipality is well, with the level of achievement score 86,2%, (2) Teacher’s Social Competence at the State of Vocational High School 6 in Padang Municipality placed in well category, with the score level achievement 84,97%, (3) There is a well correlation between headmaster’s personality competence with teacher’s social  competence at the State of Vocational High School 6 in Padang Municipality with coefficient correlation rcount = 0,36> r-table = 0,207 in level of credibility 95%. The level of headmaster’s personality competence is relative minor to the teacher’s social competence at the State of Vocational High School 6 in Padang. It means that headmaster’s personality competence gives the contribution to the teacher’s social competence at the State of Vocational High School 6 in Padang Municipality is around 12,96%.